Intervenciones de psicoterapia por ordenador para la depresión en Atención Primaria en España. - Barceló-Soler, Alberto; Baños, Rosa M.; López-Del-Hoyo, Yolanda; Mayoral, Fermín; Gili, Margalida; García-Palacios, Azucena; García-Campayo, Javier; Botella, Cristina (Actas Espanolas de Psiquiatria)
Currently, depression is a global health problem recognized by the WHO. The prevalence of this pathology in Primary Care is estimated at 19.5% worldwide, and 20.2% in Spain. In addition, the current intervention policies and protocols involve significant costs, both personal and economic, for people suffering from this disorder, as well as for society in general. On the other hand, the relapse rates after pharmacological interventions that are currently applied and the lack of effective specialized attention in mental health services reflect the need to develop new therapeutic strategies that are more accessible and profitable. Therefore, one of the proposals that are being investigated in different parts of the world is the design and evaluation of therapeutic protocols applied through Information and Communication Technologies, especially through the Internet and computer programs. The objective of this work was to present the current situation in Spain regarding the use of these interventions for the treatment of depression in Primary Care. The main conclusion is that although there is scientific evidence on the effectiveness of these programs, there are still important barriers that hinder their application in the public system, and also the need to develop implementation studies that facilitate the transition from research to clinical practice.